Search for single production of vector-like quarks decaying into Wb in pp collisions at [Formula: see text] TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; et al. (The European physical journal. C, Particles and fields, 2016)
A search for singly produced vector-like Q quarks, where Q can be either a T quark with charge [Formula: see text] or a Y quark with charge [Formula: see text], is performed in proton-proton collisions recorded with the ATLAS detector at the LHC. The dataset corresponds to an integrated luminosity of 20.3 fb[Formula: see text] and was produced with a centre-of-mass energy of [Formula: see text] TeV. This analysis targets [Formula: see text] decays where the W boson decays leptonically. A veto on massive large-radius jets is used to reject the dominant [Formula: see text] background. The reconstructed Q-candidate mass, ranging from 0.4 to 1.2 TeV, is used in the search to discriminate signal from background processes. No significant deviation from the Standard Model expectation is observed, and limits are set on the [Formula: see text] cross-section times branching ratio. The results are also interpreted as limits on the QWb coupling and the mixing with the Standard Model sector for a singlet T quark or a Y quark from a doublet. T quarks with masses below 0.95 TeV are excluded at 95 % confidence level, assuming a unit coupling and a BR[Formula: see text], whereas the expected limit is 1.10 TeV.